2020
DOI: 10.1186/s12889-020-08635-3
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the educational inequalities in the factors associated with severe acute malnutrition among under-five children in low- and middle-income countries

Abstract: Background: Low-and Middle-Income Countries (LMIC) have remained plagued with the burden of severe acute malnutrition (SAM). The decomposition of the educational inequalities in SAM across individual, household and neighbourhood characteristics in LMIC has not been explored. This study aims to decompose educational-related inequalities in the development of SAM among under-five children in LMIC and identify the risk factors that contribute to the inequalities. Methods: We pooled successive secondary data from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In Niger, there were 86.1% of children whose mothers did not have a high school diploma, compared to 0.1% in Armenia and the Kyrgyz Republic. The overall prevalence of SAM varied by country but was 5.8% in the group of children whose mothers had no education and 4.2% in the group of children whose mothers had some education 14 . According to research from Quetta, Pakistan, 295 out of 500 mothers were found to be illiterate, making up around 59% of the population.…”
Section: Discussionmentioning
confidence: 95%
“…In Niger, there were 86.1% of children whose mothers did not have a high school diploma, compared to 0.1% in Armenia and the Kyrgyz Republic. The overall prevalence of SAM varied by country but was 5.8% in the group of children whose mothers had no education and 4.2% in the group of children whose mothers had some education 14 . According to research from Quetta, Pakistan, 295 out of 500 mothers were found to be illiterate, making up around 59% of the population.…”
Section: Discussionmentioning
confidence: 95%
“…As the education level of mothers increased, the chances of their children being at risk of having SAM decreased. The past literature has also highlighted the importance of a mother's education for the occurrence of SAM [32][33][34][35] . Mothers' education appears to be so impactful for children's nutrition as an educated mother is better equipped with knowledge and awareness regarding child care.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the understanding of factors associated with inequalities in a wide range of health outcomes have adopted the technique of multivariable decomposition analysis [ 24 , 26 , 38 40 ]. Multivariable decomposition analysis is ideal for the quantifications of the contributions of different factors to gaps in an outcome of interest between two groups [ 41 ].…”
Section: Methodsmentioning
confidence: 99%